Principles of biochemistry - Horton, H. Robert; Moran, Laurene A.; Horton, H. Robert; Perry, Marc D.; Rawn, J. David; Scrimgeour, K. Gray (Prentice, Hall Pearson, 2006)
This concise, introductory text focuses on the basic principles of biochemistry, filling the gap between the encyclopedic volumes and the cursory overview texts. The book has a well-deserved reputation for being the most accurate biochemistry textbook in the market. Widely praised in its previous edition for currency, and clarity of exposition, the new edition has been thoroughly revised and updated to reflect recent changes in this dynamic discipline.
Includes bibliographical references.; Glossary 811-826p.; Index 827-852p.
Keywords: Biochemistry